C.01 Neck and arm pain after surgery for cervical myelopathy: outcomes and predictors of improvement. (5th June 2019) - Dakson, A; Christie, S; Jacobs, B; Johnson, M; Bailey, C; Charest-Morin, R; Paquet, J; Nataraj, A; Cadotte, D; Wilson, J; Manson, N; Hall, H; et al.
Abstract : Background: Cervical sponylotic myelopathy (CSM) may present with neck and arm pain. This study investiagtes the change in neck/arm pain post-operatively in CSM.Methods: This ambispective study llocated 402 patients through the Canadian Spine Outcomes and Research Network. Outcome measures were the visual analogue scales for neck and arm pain (VAS-NP and VAS-AP) and the neck disability index (NDI). The thresholds for minimum clinically important differences (MCIDs) for VAS-NP and VAS-AP were determined to be 2.6 and 4.1.Results: VAS-NP improved from mean of 5.6±2.9 to 3.8±2.7 at 12 months (P<0.001). VAS-AP improved from 5.8±2.9 to 3.5±3.0 at 12 months (P<0.001). The MCIDs for VAS-NP and VAS-AP were also reached at 12 months. Based on the NDI, patients were grouped into those with mild pain/no pain (33%) versus moderate/severe pain (67%). At 3 months, a significantly high proportion of patients with moderate/severe pain (45.8%) demonstrated an improvement into mild/no pain, whereas 27.2% with mild/no pain demonstrated worsening into moderate/severe pain (P <0.001). At 12 months, 17.4% with mild/no pain experienced worsening of their NDI (P<0.001).Conclusions: This study suggests that neck and arm pain responds to surgical decompression in patients with CSM and reaches the MCIDs for VAS-AP and VAS-NP at 12 months.